Analysis of bioconvection and oxytactic microorganisms in a porous cavity with nano-enhanced phase change materials and quadrant heater: Application of support vector regression based model - Hussain, Shafqat; Ertam, Fatih; Ben Hamida, Mohamed Bechir; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal H. (Elsevier, 2023)
In this numerical study, two-dimensional simulations are performed to obtain the bioconvection flow in a quadrant heater located porous closed space saturated with nano-enhanced phase change material (NePCM). The Galerkin finite element method (GFEM) is employed to compute the governing equations for the considered system by developing a computer code. The study is performed for wide range of parameters as aspect ratio, Darcy number, Hartmann number, nanoparticle fraction, bioconvection Rayleigh number and natural convection Rayleigh number were tested. Also, the analysis is supported via artificial intelligent by using multiple support vector regression based model. The tests were performed with artificial intelligence on temperature values. After the analysis, it is found that radius of the curvilinear shaped heater plays role on both heat transfer and fluid flow, oxygen distribution, density of motile microorganism and heat capacity. Application of support vector machine technique gives good agreement with computational fluid dynamics results. Heat and mass transfer are improved with increasing of nanoparticle addition but decrease with increasing of strength of magnetic field.
Keywords: NePCMs; Bioconvection; Porous medium; Finite element method; Support vector machine; Energy storage